Deciphering the Genetic Alterations in PIK3CA Gene Interacting Network and Their Putative Association with Breast Cancer: A Computational Approach - Sivapriya Dayakar; Anitha Pandi; Chandra Pandi; Paramasivam Arumugam; Vijayashree Priyadharsini Jayaseelan (Middle East Journal of Cancer)
Background: Cancer is a polygenic complex disorder involving a network of genes. The phosphatidylinositol 3-kinase (PIK3CA) has been reported as an oncogene that plays a role in many cancer types. The present study aims to demonstrate the association between the genetic alterations observed in the PIK3CA gene network and its role in establishing breast cancer.Method: In the present observational study, we used multiple tools (STRING, cBioportal, PANTHER, and UALCAN) to demonstrate the genetic alterations in the Breast Cancer Dataset (TCGA, Firehose Legacy). The PIK3CA gene interaction network was deduced, followed by the identification of genetic alterations, gene ontology, gene expression and survival analysis.Results: The PIK3CA gene was found to harbor 36% of genetic alterations in the form of gene amplification and mutations. The gene expression profile indicated the significant downregulation of PIK3CA gene transcripts. Interestingly, the Kaplan Meier survival analysis demonstrated that low/medium expression of PIK3CA presented with a good prognosis when compared with the high expression group. These results support the fact that PIK3CA is oncogenic.Conclusion: The PIK3CA gene has been considered as one of the potential druggable targets for breast cancer. The genetic alterations reported in the gene might influence its function. Therefore, further experimental validation is required to provide more insight into the functional association of mutations. Also, the effect of tumor suppressors and epigenetic factors targeting PIK3CA has to be assessed to gain more insight into the increased expression of PIK3CA in breast cancer patients.